Executive Loans - Kahle, Kathleen M.; Shastri, Kuldeep (Journal of Financial and Quantitative Analysis, 2004)
Abstract This paper analyzes the characteristics and impact of loans made to executives for stock purchase, option exercise, and relocation. We find that loans made to assist executives in purchasing stock or exercising options are larger and have higher interest rates than relocation loans. All types of loans, however, are issued at below-market interest rates, on average. We also find that while stock purchase loans are given to managers with low existing ownership, option exercise loans are given to managers with high existing ownership and high cash compensation. Finally, our results indicate that executive stock ownership increases following stock purchase and option exercise loans. For managers as a whole, a loan that enables a manager to buy 100 shares of stock results in only an eight share increase in ownership. However, the relation between ownership changes and stock purchase loans is much stronger for low ownership managers.